Preterm and term rupture of the amniotic sac in the third trimester: outcomes for mother and child - E. V. Enkova; A. S. Fomina; V. V. Enkova; O. V. Khoperskaya (Медицинский вестник Юга России, 2021)
Objective: To evaluate the characteristics of women in labor and pregnancy outcomes at different gestational periods with preterm prelabor rupture of membranes (PPROM) and preterm rupture of membranes (PROM) in the third trimester of pregnancy.Materials and Methods: The study included pregnant women in the third trimester, at the gestation period of 28-41.6 weeks of pregnancy, divided into groups of PROM and PPROM: 173 (80.8%) and 41 (19.2%) pregnant women, respectively.Results: It was found that PPROM is associated with a significantly lower gestational age, higher levels of C-reactive protein, and higher body temperature upon admission to the maternity hospital (P <0.05). Breech presentation and history of cesarean section were significantly associated with PPROM (P < 0.05), rather than PROM. The PPROM group had a significantly longer latency period compared to the PROM group, in which the latency period increased with a lower gestational age (28–31.6 weeks). A significantly higher rate of admission to the neonatal intensive care unit (NICU) was observed in the PPROM group compared to the PROM group. Also, at the gestational age of 28-31.6 weeks, a significantly higher rate of admission to the NICU was revealed compared to the gestational age of 32-36. 6 weeks (P < 0.05).Conclusions: The purpose of this retrospective study was to evaluate the characteristics of women in labor and pregnancy outcomes at different gestational periods with PPROM and PROM in the third trimester of pregnancy.